2023
DOI: 10.3390/molecules28135090
|View full text |Cite
|
Sign up to set email alerts
|

Facile Ball Milling Preparation of Flame-Retardant Polymer Materials: An Overview

Abstract: To meet the growing needs of public safety and sustainable development, it is highly desirable to develop flame-retardant polymer materials using a facile and low-cost method. Although conventional solution chemical synthesis has proven to be an efficient way of developing flame retardants, it often requires organic solvents and a complicated separation process. In this review, we summarize the progress made in utilizing simple ball milling (an important type of mechanochemical approach) to fabricate flame ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…The mechanochemical method known as ball milling is widely disseminated in the literature and used to obtain many micronized products [ 37 , 38 , 39 , 40 ]. This technique is used to fragment the BC into microparticles through mechanical collisions that break the hydrogen bonds, which are responsible for most of the intra- and intermolecular bonds and, consequently, for the three-dimensional crystalline structure of this biopolymer [ 31 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanochemical method known as ball milling is widely disseminated in the literature and used to obtain many micronized products [ 37 , 38 , 39 , 40 ]. This technique is used to fragment the BC into microparticles through mechanical collisions that break the hydrogen bonds, which are responsible for most of the intra- and intermolecular bonds and, consequently, for the three-dimensional crystalline structure of this biopolymer [ 31 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ball milling has been applied in the development of flame-retardant materials owing to its capabilities of crushing, surface modification, and unrestricted mixing of flame-retardant additives with polymer matrices. 76 Electrospinning. Electrospinning employs an electric field to convert polymer solutions or melts into fibers.…”
Section: Hyper-cross-linking Of the Wpsmentioning
confidence: 99%
“…Steel, known for its high hardness and ease of processing, is commonly employed for manufacturing ball milling jars, whereas materials such as agate and nylon are less widely used. Ball milling has been applied in the development of flame-retardant materials owing to its capabilities of crushing, surface modification, and unrestricted mixing of flame-retardant additives with polymer matrices …”
Section: Hyper-cross-linking Of the Wpsmentioning
confidence: 99%
“…Since Montarnal et al 2 found the first vitrimer in 2011, this polymer has gained significant interest and attention in a short time span of about 10 years. 1,[3][4][5][6] Compared to traditional thermoplastic polymers, vitrimers exhibit higher mechanical strength and longer service life, leading to a reduction in resource waste. 7,8 So far, vitrimers have found wide applications, including shape memory polymers (SMPs), 9,10 3D printing, 11 in-space assembly for the complex structure, 12 flame-resistant material, [13][14][15] etc.…”
Section: Introductionmentioning
confidence: 99%